Relationship between the postpartum moment of pregnancy and productivity in water buffalo cows. Preliminary results - Héctor Nava-Trujillo; Adriana Morgado-Osorio; Armando Quintero-Moreno (Revista Científica)
One of the most important facts in the livestock industry is the need to increase reproductive performance to improve profitability. In the case of water buffalo cows, a calving-to-con-ception interval maximum of 90 days is recommended; however, achieving this reproductive target could be challenging. This study evaluated how the moment water buffalo cows get pregnant (before or after 90 days postpartum) affects the lactation length, total milk yield, calving interval, milk yield per day of the calving interval, and dry period. In this study, day 90 is considered the maximum postpartum moment in which the buffaloes must become pregnant to reach a calving interval near 400 days, regarded as the maximum calving interval without a negative economic impact on farm profitability. This retrospective cohort study analyzed 3060 observations from 1459 water buffalo cows from three farms in a similar agroecological environment (Catatumbo and Jesus Maria Semprun counties, Zulia State, Venezuela). A linear mixed model of the mean of parity, lactation length, total milk yield, calving interval, milk yield per day of calving interval, milk yield per year, dry period, and calving interval was built with the postpartum moment of pregnancy (before or after 90 days) as a fixed effect. All analyses were performed in Stata 15.1, and comparisons were adjusted by Sidak’s method. Water buffalo cows getting pregnant after 90 days postpartum had lower parity (1.85 vs. 2.25, p<0.05), a more extended lactation period (321.77 days vs. 254.01 days, p<0.05), a total milk yield of 18.09% higher (1452.91 kg vs. 1230.31 kg, p<0.05) and the calving interval was 149.43 days longer than those getting pregnant in the first 90 days post-partum (512.93 vs. 363 days, p<0.05). Both the milk yield per day of calving interval and the milk yield per year were higher in water buffaloes getting pregnant during the first 90 days postpartum (3.39 kg and 1237.5 kg vs. 2.9 kg and 1072.11 kg, respectively, p<0.05) and the dry period was shorter (108.98 vs. 191.16 days, p<0.05). In conclusion, water buffalo cows getting pregnant in the first 90 days postpartum had more milk yield per day of calving interval, more milk per year, and fewer non-productive days than those getting pregnant after 90 days postpartum. Adopt measurements to increase the reproductive performance of water buffalo cows and, in consequence, to maximize profitability must be a rule and not an exception.